Keperluan pelaksanaan kebenaran merancang bagi aktiviti perlombongan di negeri Perak - Khalib, Abdul Rahim Syah (2013)
Perak is a one of the state which rich in mineral resources that could be explore to provide economic contribution to the Perak State Government especially through mining activities. In the past, mining is among the main activities to generate economy to the state. Mining is found in natural form or resulting from exploration activities, creating a man-made mine. The effects of uncontrolled mining activities will cause problems such as flooding and pollution in the absence of close monitoring of the Local Authority. In helping local authorities to regulate mining activities, this research will focus on the needs of the implementation of Planning Permission as provided in Section 2 (1), Town and Country Planning Act 1976 (Act 172). With the advent of mining planning permission, it will be able to ensure that any particular development of mining activities will be controlled by the authorities such as the Local Authority (LA). This is because, the aspects that will be addressed in this mining planning permission process will cover three stages in planning process which is before, during and after mining activities carried out. Therefore, this study was undertaken to examine the current planning criteria used by the Department of Mineral and Geosciences and State Land Office in considering and approving applications for mining activities in the state, identify the factors why planning permission procedures for mining activities as described in Section 2 (1) Act 172 was not fully enforced in the state and examine the implications of planning permission for Mining. To achieve these three objectives, data collection methods for this study was obtained from the primary data and secondary data and also from the distribution of questionnaires and interviews with special technical agencies relating to planning policy makers at the state level. Based on the study results, recommendations are made for improvement of processes and procedures during the procedure to ensure that elements of planning permission for mining activities to comply with aspects of planning control has been set as the provisions of Act 172 to ensure sustainable mining activities can be implemented.